Fibrinogen Binding Is Independent of an Increase in Intracellular Calcium Concentration in Thrombin Degranulated Platelets - Pulcinelli, Fabio M; Daniel, James L; Riondino, Silvia; Gazzaniga, Pier Paolo; Salganicoff, Leon (Thrombosis and Haemostasis, 1995)
In a suspension of thrombin degranulated platelets (TDP), ADP and epinephrine can induce platelet aggregation, whereas the synthetic agonist of the thromboxane/endoperoxide receptor U46619 causes only shape change. However, U46619 can enhance platelet aggregation induced by ADP and epinephrine. In this paper, we have measured fibrinogen binding in relation to phospholipase C(PLC) activation and calcium mobilization in TDP activated by ADP, epinephrine and U46619.ADP caused fibrinogen binding in TDP but neither activated PLC nor caused a calcium mobilization. The requirement for ADP in inducing exposure of fibrinogen binding sites was not absolute since the combination of epinephrine and U46619 produced an increase in fibrinogen binding. U46619 caused significant PLC activation and cytosolic calcium release but not fibrinogen binding. These results suggest that in TDP the exposure of fibrinogen binding sites, after agonist activation, is independent of both PLC activation and calcium mobilization.